Rapid and sensitive assay for the phytotoxin rhizobitoxine. - Ruan, X (1991)
Rhizobitoxine is a phytotoxin synthesized by some strains of the legume symbiont genus Bradyrhizobium and the plant pathogen Pseudomonas andropogonis. We demonstrate here a new enzymatic assay which is 100-fold more sensitive than previous assays and can detect as little as 1.0 pmol of rhizobitoxine. The assay is based on the inhibition of Salmonella typhimurium beta-cystathionase by rhizobitoxine. Interestingly, beta-cystathionase from Bradyrhizobium japonicum is insensitive to rhizobitoxine at concentrations lower than 75 microM.